(untitled) (American Journal of Islam and Society, 2005)
Written at a critical historical juncture of Arab-western relations, Khalidi’s text provides a refreshing and informed account of western intervention in the Middle East. It stresses the catastrophic human and political consequences of western colonial adventures in the region and the neglect of this historical experience by current American foreign policy decision makers. Although written primarily for a non-academic, American audience, it is a useful and important text on contemporary Middle East history. Accessible and highly readable, it provides insights into a series of major issues currently relevant to the study of the Middle East: democracy, oil, Palestine, and Iraq. The first chapter provides an account of western colonialism’s social, political, economic, and cultural legacy wrought on the Middle East. Beginning with a brief introduction to the American march to war with Iraq, the author establishes an approach employed throughout the text: juxtaposing the historical western colonial experience with the American invasion and occupation of Iraq. Locating western involvement in the Middle East within the context of the Ottoman Empire’s decline, Khalidi highlights the differential systems of colonial rule imposed on the region. Throughout, he emphasizes the indigenous resistance to colonialism, thus arguing against Orientalist discourses of indigenous acquiescence and subservience to the supposed benevolence of colonialist rule. Two important points emerge: first, that the political structures imposed by the colonial regimes have persisted, and second, that the region’s political culture remains deeply rooted in the anti-colonial experience. This experience – entirely conditioned through European involvement in the region – meant that for many, the United States never experienced the same political and cultural hostility as Europe. Throughout the cold war, however, the United States’ image as a disinterested outside power began to give way to an image of the United States as a significant power broker in the region with many interests, and, most importantly, few objectives compatible with the political desires of the region’s peoples ...